Influence of AC signal oscillator level on effective mobility measurement by split C–V technique in MOSFETs. Issue 17 (1st August 2016) - Karatsori, T.A.; Theodorou, C.G.; Dimitriadis, C.A.; Ghibaudo, G.
Abstract : The impact of the AC signal oscillator level on the effective mobility measurement by split C–V technique in MOSFETs is investigated. It is found that, due to strong nonlinearity below threshold, the gate‐to‐channel capacitance and, by turn, the channel inversion charge increases linearly with the oscillator level. As a consequence, the extracted effective mobility decreases linearly with the oscillator level, resulting in a huge underestimation of the effective mobility in weak inversion. A physical model explaining these behaviours is developed, which enables to obtain a quantitative description of both inversion charge and effective mobility variations with the oscillator level and the gate voltage.